2022
DOI: 10.1111/aogs.14405
|View full text |Cite
|
Sign up to set email alerts
|

Paracetamol preceding very preterm birth: Is it safe?

Abstract: Introduction:The use of paracetamol for pain relief in pregnancy is common.However, the influence of paracetamol on the perinatal adaptation of high-risk infants has not been studied. These data are important for safety, since another inhibitor of prostaglandin synthesis is harmful to infants born very preterm and increases serious morbidity. We studied whether the use of paracetamol had an adverse influence on neonatal adaptation and the outcomes of infants during the first hospitalization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Also, less sensitive equipment was used to detect foetal breathing in the clinical setting, compared to the experimental setting [65,66]. An observational study in premature infants exposed to antenatal paracetamol 24 h prior to birth showed less acute rescue interventions at birth, predominantly due to less need for surfactant administration [68]. In this study, infants exposed to antenatal paracetamol also required lower maximum ventilation pressures after birth compared to matched controls and antenatal paracetamol exposure correlated positively with all Apgar scores at birth [68].…”
Section: Possible Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, less sensitive equipment was used to detect foetal breathing in the clinical setting, compared to the experimental setting [65,66]. An observational study in premature infants exposed to antenatal paracetamol 24 h prior to birth showed less acute rescue interventions at birth, predominantly due to less need for surfactant administration [68]. In this study, infants exposed to antenatal paracetamol also required lower maximum ventilation pressures after birth compared to matched controls and antenatal paracetamol exposure correlated positively with all Apgar scores at birth [68].…”
Section: Possible Interventionsmentioning
confidence: 99%
“…An observational study in premature infants exposed to antenatal paracetamol 24 h prior to birth showed less acute rescue interventions at birth, predominantly due to less need for surfactant administration [68]. In this study, infants exposed to antenatal paracetamol also required lower maximum ventilation pressures after birth compared to matched controls and antenatal paracetamol exposure correlated positively with all Apgar scores at birth [68]. While caution is needed when interpreting observational studies, there seems to be an association between improved respiratory function in premature infants and antenatal paracetamol exposure.…”
Section: Possible Interventionsmentioning
confidence: 99%
“…Late preterm infants are the highest percentage of preterm infants and deserve special attention. However, the current studies mainly focused on very preterm infants or early preterm infants, and the research on animal models of late preterm infants is limited ( 34 ). Therefore, the goal of this study was to create a group of late preterm newborn pigs (at 113 gestational age) by C-section ( 6 ), with full-term newborn pigs (at 114 gestational age) born naturally as the control.…”
Section: Introductionmentioning
confidence: 99%